Transforming Growth Factor-β-Induced Cell Plasticity in Liver Fibrosis and Hepatocarcinogenesis - Fabregat, Isabel; Caballero-Díaz, Daniel (Frontiers in Oncology, 2018)
The Transforming Growth Factor-beta (TGF-β) family plays relevant roles in the regulation of different cellular processes that are essential for tissue and organ homeostasis. In the case of the liver, TGF-β signalling participates in different stages of disease progression, from initial liver injury towards fibrosis, cirrhosis and cancer. When a chronic injury takes place, mobilization of lymphocytes and other inflammatory cells occur, thus setting the stage for persistence of an inflammatory response. Macrophages produce profibrotic mediators, among them, TGF-β, which is responsible for activation -transdifferentiation- of quiescent hepatic stellate cells (HSC) to a myofibroblast (MFB) phenotype. MFBs are the principal source of extracellular matrix protein (ECM) accumulation and prominent mediators of fibrogenesis. TGF-β also mediates an epithelial-mesenchymal transition (EMT) process in hepatocytes that may contribute, directly or indirectly, to increase the MFB population. In hepatocarcinogenesis, TGF-β plays a dual role, behaving as a suppressor factor at early stages, but contributing to later tumour progression, once cells escape from its cytostatic effects. As part of its potential pro-tumorigenic actions, TGF-β induces EMT in liver tumour cells, which increases its pro-migratory and invasive potential. In parallel, TGF-β also induces changes in tumour cell plasticity, conferring properties of a migratory tumour initiating cell (TIC). The main aim of this review is to shed light about the pleiotropic actions of TGF-β that explain its effects on the different liver cell populations. The cross-talk with other signalling pathways that contribute to TGF-β effects, in particular the Epidermal Growth Factor Receptor (EGFR), will be presented. Finally, we will discuss the rationale for targeting the TGF-β pathway in liver pathologies.